2012
DOI: 10.1007/s00253-012-3942-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of (R)-1,3-butanediol from 4-hydroxy-2-butanone by a newly isolated strain Candida krusei ZJB-09162

Abstract: Biocatalytic asymmetric preparation of (R)-1,3-butanediol has been attracting much attention in pharmaceuticals industry. A new ideal strain, ZJB-09162, which exhibited high reduction activity and excellent (R)-stereospecificity towards 4-hydroxy-2-butanone, has been successfully isolated from soil samples. Based on morphology, physiological tests (API 20 C AUX), and 5.8S-ITS sequence, the isolate was identified as Candida krusei. Kinetic characterization demonstrated that carbonyl reductase from C. krusei ZJB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…1) Because beta-lactam antibiotics are the most commonly used antibacterial agents, the demand for (R)-1,3-BD has increased, and as a result, methods for (R)-1,3-BD production have been studied. 2,3) Thus far, 1,3-BD has been produced industrially in multistep chemical reactions as a racemic mixture of R and S forms, mostly from acetaldehyde prepared synthetically from fossil fuels. 4,5) In contrast, optically active 1,3-BD has been biologically synthesized from petroleum-based chemicals, such as 4-hydroxybutanone or its racemic and enantiomeric compounds, through microbial stereo-selective reduction or optical resolution.…”
mentioning
confidence: 99%
“…1) Because beta-lactam antibiotics are the most commonly used antibacterial agents, the demand for (R)-1,3-BD has increased, and as a result, methods for (R)-1,3-BD production have been studied. 2,3) Thus far, 1,3-BD has been produced industrially in multistep chemical reactions as a racemic mixture of R and S forms, mostly from acetaldehyde prepared synthetically from fossil fuels. 4,5) In contrast, optically active 1,3-BD has been biologically synthesized from petroleum-based chemicals, such as 4-hydroxybutanone or its racemic and enantiomeric compounds, through microbial stereo-selective reduction or optical resolution.…”
mentioning
confidence: 99%
“…Titres reached are similar to studies using plasmid borne expression of pyruvate decarboxylase from Zymomonas mobilis and deoxyribose-5-phosphate aldolase from Bacillus halodurans ( Nemr et al, 2018 ; Kim et al, 2020 ) but lower than in studies using plasmid borne expression of PhaA and PhaB from R. eutropha coupled with expression of Bld from C. saccharoperbutylacetonicum ( Kataoka et al, 2013 , 2014 ) summarised in Table 1 . Higher titres can be reached using 4-hydroxy-2-butanone as substrate ( Itoh et al, 2007 ; Zheng et al, 2012 ; Yang et al, 2014 ), however glucose is more widely available and more ecenomical than 4-hydroxy-2-butanone. Finally, future work should aim at optimising the fermentation and at upscaling of the production which is easier with an anaerobic organism such as the one used in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction through yeast fermentation of 4H2B led to low product yields when the desired stereo-specificity was reached ( Matsuyama et al, 2001 ). However, later research showed promising results when reducing 4H2B using either newly isolated yeast strains, with up to 100% enantiomeric excess and a titre of 38.2 g/l ( Zheng et al, 2012 ; Yang et al, 2014 ), or genetically engineered E. coli , where a 99% enantiomeric excess and 99% substrate yield were obtained ( Itoh et al, 2007 ). Another approach using genetically modified E. coli based on the enantio-selective oxidation of ( S )-1,3-BDO was initially promising ( Matsuyama et al, 2001 ) but proved difficult to scale-up ( Yamamoto et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…The specific applications of these metabolic engineering tools in microbial pathways are presented in Figure 3B. focused on the biotransformation of 4-hydroxy-2-butanone [123][124][125] or 1,3-BDO racemic mixture [126][127][128] to (R)-1,3-BDO. More recently, two artificial metabolic pathways for (R)-1,3-BDO production from glucose have been developed: (i) the reversed fatty acid β-oxidation pathway [129][130][131] and (ii) the 2-deoxyribose-5-phosphate aldolasealdo-keto reductase (DERA-AKR) pathway.…”
Section: Metabolic Engineering For the Production Of Non-natural-non-...mentioning
confidence: 99%